Cellular function and signaling pathways of vascular smooth muscle cells modulated by sphingosine 1-phosphate - Takuji Machida; Ryosuke Matamura; Kenji Iizuka; Masahiko Hirafuji (Elsevier, 2016)
Sphingosine 1-phosphate (S1P) plays important roles in cardiovascular pathophysiology. S1P1 and/or S1P3, rather than S1P2 receptors, seem to be predominantly expressed in vascular endothelial cells, while S1P2 and/or S1P3, rather than S1P1 receptors, seem to be predominantly expressed in vascular smooth muscle cells (VSMCs). S1P has multiple actions, such as proliferation, inhibition or stimulation of migration, and vasoconstriction or release of vasoactive mediators. S1P induces an increase of the intracellular Ca2+ concentration in many cell types, including VSMCs. Activation of S1P3 seems to play an important role in Ca2+ mobilization. S1P induces cyclooxygenase-2 expression in VSMCs via both S1P2 and S1P3 receptors. S1P2 receptor activation in VSMCs inhibits inducible nitric oxide synthase (iNOS) expression. At the local site of vascular injury, vasoactive mediators such as prostaglandins and NO produced by VSMCs are considered primarily as a defensive and compensatory mechanism for the lack of endothelial function to prevent further pathology. Therefore, selective S1P2 receptor antagonists may have the potential to be therapeutic agents, in view of their antagonism of iNOS inhibition by S1P. Further progress in studies of the precise mechanisms of S1P may provide useful knowledge for the development of new S1P-related drugs for the treatment of cardiovascular diseases.